2018
DOI: 10.1155/2018/6049198
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure ofLeishmania tropicaCausing Anthroponotic Cutaneous Leishmaniasis in Southern Iran by PCR-RFLP of Kinetoplastid DNA

Abstract: Iran is one of the six countries with the most cutaneous leishmaniasis (CL) patients. Understanding better the genotypes of the parasite population in relation to geography and climate is critical to achieving better CL control. We aimed to characterise the population structure of Leishmania tropica, the cause of anthroponotic cutaneous leishmaniasis (ACL), from important foci in southeast (Bam and Kerman) and southwest (Shiraz) Iran. A total of 39 L. tropica isolates from ACL patients from southeast (Bam 14, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Hence, the ITS1 genetic marker could serve to inspire further future investigations on the function of these variations among different non-healing clinical forms of patients with ACL. The VL caused by L. tropica was also revealed to be genetically heterogeneous [ 67 ] and to play a key role in the generation of drug-resistant leishmaniasis recidivans in the southeastern part of Iran [ 68 ]. Leishmania tropica isolates in the southeast (Kerman and Bam counties) represented different genetic polymorphisms using PCR-RFLP of the kinetoplast DNA (kDNA) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the ITS1 genetic marker could serve to inspire further future investigations on the function of these variations among different non-healing clinical forms of patients with ACL. The VL caused by L. tropica was also revealed to be genetically heterogeneous [ 67 ] and to play a key role in the generation of drug-resistant leishmaniasis recidivans in the southeastern part of Iran [ 68 ]. Leishmania tropica isolates in the southeast (Kerman and Bam counties) represented different genetic polymorphisms using PCR-RFLP of the kinetoplast DNA (kDNA) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such genotype differences within the same species might behave differently to chemotherapy, as a number of intraspecific genetic variants have already been documented for L . tropica from the same area [7,35,36]. Also failure caused by patients bearing multiple lesions could be a consequence of a decreased capability of the immune system against the Leishmania species [32].…”
Section: Discussionmentioning
confidence: 99%
“…Sharifi et al (36) conducted a crosssectional survey in Kerman province, using PCR to identify the Leishmania species causing CL; all samples from Bam, Kerman, Jiroft, Shahre-Babak, Anbarabad, and Roodbare-Jonoob were identified as L. tropica, and only nine (4.4%) cases of L. major were detected in Baft and Sirjan districts. Phylogenetic studies showed a high degree of homogeneity among L. tropica strains in southeast Iran (37). Hormozgan, other southeast Iranian province, has been shown to be a major foci of L. major; e.g., a subsample of 18 of 40 ulcers were all found to be identified as L. major in a study in Jask county (38).…”
Section: South-southeastern Iranmentioning
confidence: 97%